The application of augmented reality in competency-based learning - Efendi, Raimon; Ambiyar, Ambiyar; Estuhono, Estuhono; Bento, Blas Orti'z; Nanda, Dodi Widia (Intelektual Pustaka Media Utama, 2026)
This research aims to overcome several challenges in vocational education, primarily related to the lack of learning tools and the development of 21st-century skills such as critical thinking, communication, collaboration, and creativity. This research uses the research and development (RD) model with the ADDIE development procedure, with the steps analysis, design, development, implementation, and evaluation. Data was collected through surveys, interviews, and observations of students and teachers during the teaching and learning process. The research results show that the augmented reality-competency based learning (AR-CBL) application effectively increases students’ understanding of computer network material. Apart from that, AR-CBL also has the potential to be an interactive learning tool that can improve student learning motivation. The AR-CBL learning model resulting from this research can support the development of technical skills and critical thinking, communication, collaboration, and creativity (4C) abilities. The implementation of AR-CBL also has the potential to improve educational standards in vocational schools and help graduates better match industry needs. With the results of this research, schools and education stakeholders can consider using AR-CBL technology in the vocational school curriculum to prepare graduates to face the world of work in this digital era.